Analisis Permasalahan Kredit Macet - Khofifah Indah Pohan; Mustapa Kamal Rokan (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2022)
This research aims to find out what factors are the cause of bad credit problems and how the bank sumut Syariah branch office medan in handling non-performing loans. The type of research conducted is qualitative research using descriptive methods. The results of the research findings show that the causes of bad credit problems are: (1) Weaknesses from the internal debtor side can be caused by bad faith from the debtor, and the decline of the debtor's business resulted in a decrease in the debtor's ability to pay installments; (2) Weaknesses from the internal side of banks/financial institutions can be caused by bad faith from bank officers/financial institutions for personal interests, such as bank employees/financial institutions repaid debtors' credits that reward the disbursement of the credit. In the case of bad loans, the bank needs to make a rescue, so that it will not cause losses. Rescues that are carried out can be by providing relief in the form of a period of return, especially for credits that have experienced disasters